An Operational Solution to Overcome the Very Poor Subgrade Soil Condition of the Azadegan Freeway - Asadi, Hossein; Ghadimi, Behzad; Nikraz, Hamid (Research Publishing Services, 2012)
Poor subgrade soil condition which is very sensitive to moisture presents a construction challenge for all pavement engineers. One of the case histories which became a dilemma for the Azadegan freeway in Tehran is the presence of waste material in subgrade soil. This paper discusses the site investigation to gather some useful information about the principal causes of these problems and deals with some in-depth Laboratory tests which have been done in the soil and asphalt laboratory of Tehran municipality. The pavement condition index known as PCI has been calculated to address all the deteriorations and causes to make a good decision. After analyzing all the gathered data, several methods has been discussed, for example, deep mixing, short concrete piles, shredded tires, and injection. Finally based on the lack of facilities and budget shortage, a retaining wall with geogrids has been chosen for this very special case which is right now under traffic flow.